Semileptonic transitions: B(s) → π(K); Ds → K; D → π,K; and K → π - Zhao-Qian Yao; Daniele Binosi; Zhu-Fang Cui; Craig D. Roberts (Physics Letters B, 2022)
Continuum Schwinger function methods for the strong-interaction bound-state problem are used to arrive at a unified set of parameter-free predictions for the semileptonic K→π, D→π,K and Ds→K, B(s)→π(K) transition form factors and the associated branching fractions. The form factors are a leading source of uncertainty in all such calculations: our results agree quantitatively with available data and provide benchmarks for the hitherto unmeasured Ds→K0, B¯s→K+ form factors. The analysis delivers a value of |Vcs|=0.974(10) and also predictions for all branching fraction ratios in the pseudoscalar meson sector that can be used to test lepton flavour universality. Quantitative comparisons are provided between extant theory and the recent measurement of BBs0→K−μ+νμ. Here, further, refined measurements would be useful in moving toward a more accurate value of |Vub|.